Initial Safety Data of Bevacizumab as Adjuvant Therapy for Colorectal Cancer - Alexander, Lori (MD Conference Express, 2008)
The results of a National Surgical Adjuvant Breast and Bowel Project [NSABP; NCT00096278 trial indicate that bevacizumab is safe when it is given as postoperative adjuvant therapy (in conjunction with conventional chemotherapy) to patients with stage II or stage III colorectal cancer. The efficacy data from the study are not yet available, but the safety data were reported first because of the potential effect on ongoing or planned investigations that involve bevacizumab and other antiangiogenic agents.